Frap1 geno T/G (rs 2295080) polimorfizmo asociacija su sportininku greitumo ir jegos savybemis - Drozdovska, S.; Oleshko, V. (Sporto Mokslas-Sport Science, 2016)
Study background and hypothesis. The enzyme mTOR plays an important role in extracellular signal transduction, phosphorylates various protein metabolism enzymes, transcription, and translation factors and in this way regulates metabolism in skeletal muscles. mTOR is encoded by the mTOR (FRAP1) gene, which contains 8189 single nucleotide polymorphisms (SNPs). Their genetic contribution to mTOR protein activity is yet to be confirmed. We aimed to establish whether the SNPs (rs2295080 and rs11121704) in gene FRAP1 were associated with athlete`s status in different kinds of sport. Study methods. During the course of the study, 251 highly qualified athletes of various sport backgrounds were enrolled. Athletes represented three functional groups: endurance-oriented (N=97), mixed sports (N=47), and poweroriented (N=107). A total of 390 subjects not involved in sport activities were recruited into the sedentary group. DNA samples were extracted from participants` buccal epithelial cells. The real-time PCR by «7500 Fast Real-time PCR» was used to determine T/G (rs2295080) and T/C (rs11121704) of gene FRAP1 polymorphisms. A study of special performance in athletes with different genotypes who specialized in weight-lifting was conducted as well. Study results. All genotype frequencies were within the Hardy-Weinberg equilibrium. There were no differences in genotype distribution of T/C (rs11121704) FRAP1 in athletes and sedentary group. There was no strong evidence of the association of T/C (rs11121704) mTOR with athletes` status but T-allele frequency was higher in endurance athletes and C-allele - in strength athletes. Higher C-allele frequency may lead to a positive influence in strength sports as it was previously shown that C-allele could lead to an increased expression of this factor. Analysis of T/G (rs2295080) revealed that the frequency of G/G-genotype average is as follows: sedentary group - 7.5%, endurance-oriented - 15.5%, mixed sports - 8.5%, power-oriented - 5.6 %. There is a reduction in the number of athletes who are carriers of G/G-genotype and allele among power-oriented athletes and an increase in the number of endurance-oriented athletes. We established the reduction of G-allele frequency in power-oriented athletes and the increase of T-allele frequency in this group of carriers. Probable difference in the distribution of alleles in athletes who specialized in endurance sports and power-oriented athletes (p=0.04) was found. Athletes who are carrier of G-allele of T/G polymorphism of gene FRAP1 show the tendency to decrease indicators of special performance compared to athletes with T/T genotype. Discussion and conclusions. The association between T/G (rs2295080) polymorphism of gene FRAP1 and athletes` status was established. Association can be connected with the fact that T/G polymorphism located in the promoter region of the gene leads to changes in the level of mRNA. The research results are still controversial, require functional studies, and should be investigated in relevant cohorts. Our results can be used to design better selection and training processes in order to allow athletes to achieve their full potential.